Upper gastro-intestinal endoscopy prior to cholecystectomy, a necessity? an observational study in a tertiary care hospital in South India - Anandaravi, B. N.; Jabbar, Faiyaz Abdul (International Surgery Journal, 2019)
Background: Cholelithiasis is the most common disease state involving the gallbladder and the biliary tree. Once the USG is reported as cholelithiasis, the patient is usually taken up for cholecystectomy. The patients with cholelithiasis usually present with upper gastro intestinal (UGI) symptoms which may also be attributed to other UGI pathologies. This study focuses on evaluating upper GI endoscopy as an investigative modality to diagnose other associated upper GI pathologies in patients with USG proven gallstones presenting with dyspeptic symptoms. Methods: An observational study was undertaken over a span of 2 years, from June 2016 to May 2018. All the patients who presented with complaints of upper GI symptoms were subjected to undergo USG abdomen. The patients with positive USG findings for cholelithiasis were included and further evaluated by upper GI endoscopy. Results: Out of 100 subjects evaluated during the study period, 58 were females and 42 males. The most common presenting symptom was heartburn (69%), followed by dyspepsia (58%), belching (56%) and nausea/vomiting (53%). Out of 100 patients 44 patients presented with biliary colic and nausea/vomiting (14%). 44 of the subjects were found to have normal mucosal study. Remaining 66% of the subjects had positive endoscopic findings. The most common endoscopic finding was gastro-esophageal-reflux-disease (GERD) (31%). Conclusions: In this study it was found that 66% of the subjects had co-existing UGI pathologies. It is advisable to get UGI endoscopy routinely for patients being planned for cholecystectomy pre-operatively.